2021
DOI: 10.1038/s41523-021-00217-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized intervention involving family to improve communication in breast cancer care

Abstract: We examined the effects of a communication intervention to engage family care partners on patient portal (MyChart) use, illness understanding, satisfaction with cancer care, and symptoms of anxiety in a single-blind randomized trial of patients in treatment for breast cancer. Patient-family dyads were recruited and randomly assigned a self-administered checklist to clarify the care partner role, establish a shared visit agenda, and facilitate MyChart access (n = 63) or usual care (n = 55). Interviews administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…They often focused on dyad coping 34 , 37 , 45 , 46 and communication. 31 , 39 , 40 , 42 Half of the studies examined face-to-face interventions ( k ​= ​14); five programs involved technology-based interventions, 31 , 35 , 37 , 43 , 47 while others involved telephone ( k ​= ​3).…”
Section: Resultsmentioning
confidence: 99%
“…They often focused on dyad coping 34 , 37 , 45 , 46 and communication. 31 , 39 , 40 , 42 Half of the studies examined face-to-face interventions ( k ​= ​14); five programs involved technology-based interventions, 31 , 35 , 37 , 43 , 47 while others involved telephone ( k ​= ​3).…”
Section: Resultsmentioning
confidence: 99%
“…Mothers may be more likely to choose to take AET because they have an increased awareness of being needed. Prior studies observed an important role of patients' family members in treatment acceptance 33 . However, there is also research showing that the inner‐familiarly relationships are individual and complex, and they may be supportive as well as obstructive 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies observed an important role of patients' family members in treatment acceptance. 33 However, there is also research showing that the innerfamiliarly relationships are individual and complex, and they may be supportive as well as obstructive. 34 Patients with a higher tumor stage (≥II) and, therefore, a worse prognosis tended to have a higher acceptance rate at the time of the data collection than patients with stage I BC.…”
Section: Acceptance and Non-modifiable Factorsmentioning
confidence: 99%
“…However, no difference was detected in exchange of direct messages by patients or caretakers in the control and intervention groups. 32 The second study, also conducted by Wolff et al 33…”
Section: Accepted Manuscriptmentioning
confidence: 97%